Effects of root restriction on nitrogen and gene expression levels in nitrogen metabolism in Jumeigui grapevines (Vitis vinifera L.×Vitis labrusca L.) - Xiu-ming YU; Jie-fa LI; Li-na ZHU; Bo WANG; Lei WANG; Yang BAI; Cai-xi ZHANG; Wen-ping XU; Shi-ping WANG (Journal of Integrative Agriculture, 2015)
To decipher the relationship between the inhibited shoot growth and expression pattern of key enzymes in nitrogen metabolism under root restriction, the effects of root restriction on diurnal variation of expression of nitrate reductase (NR), nitrite reductase (NiR), glutamine synthetase (GS1-1, GS1-2, GS2) and glutamate synthase (Fd-GOGAT, NADH-GOGAT) genes and nitrogen levels were evaluated in two-year-old Jumeigui grapevines (Vitis vinifera L.×Vitis labrusca L.) when significant differences in shoot growth were observed between treatments at expansion stage (22 days after anthesis). Grapevines were planted in root-restricting pits as root restriction and in an unrestricted field as the control. Results showed that root restriction significantly reduced shoot growth, but promoted the growth of white roots and fibrous brown roots and improved the fruit quality. (NO3−+NO2−)-N concentration in all plant parts, NH4+-N concentration in white roots and total N concentration in leaves and brown roots were significantly reduced under root restriction. Gene expression analysis revealed that mRNA levels of genes related to the GS1/NADH-GOGAT pathway were lower in root-restricted than in control petioles, whereas genes involved in the GS2/Fd-GOGAT pathway were up-regulated under root restriction. Root restriction also resulted in down-regulation of genes involved in nitrogen metabolism in leaves, especially at 10:00, while transcript levels of all these genes were enhanced in root-restricted white and brown roots at most time points. This organ-dependent response contributed to the alteration in NO3− reduction and NH4+ assimilation under root restriction, leading to less NO3− transported from roots and then assimilated in root-restricted leaves. Therefore, this study implied that shoot growth inhibition in grapevines under root restriction is closely associated with down-regulation of gene expression in nitrogen metabolism in leaves.